Biceps tissue bioimpedance changes from isotonic exercise-induced fatigue at different intensities. (20th February 2018) - Fu, Bo; Freeborn, Todd J
Abstract: Electrical impedance measurements of biological tissues, also referred to as bioimpedance, quantify the passive electrical properties of these materials. The motivation behind collecting these measurements is to provide details regarding the electrochemical structures and processes within these tissues. Bioimpedance measures have recently been investigated as a method to monitor morphological and physiological changes that occur in skeletal muscle during contraction as well as result from fatigue. Objective: To investigate the effect of exercise intensity during a fatiguing protocol of the biceps brachii on the electrical impedance changes of biceps tissue due to an isotonic protocol. Approach: Resistance ( R ) and reactance ( X ) measurements were collected from the right and left biceps of 18 participants pre and post execution of a fatiguing protocol using an isotonic exercise to task failure at two intensities, either 60% ( N  = 10) or 75% ( N  = 8) of their assessed one-repetition maximum strength. Main Results: There were significant differences ( p  < 0.05) between the pre and post fatigue R and X within groups due to the exercise protocol. But no significant differences ( p  > 0.05) of the R and X between groups at different intensities and no significant differences ( p  > 0.05) of changes between the left and right biceps in both groups. Significance: These results show that the level of exercise intensity did not significantly impact the changes in electrical impedance of the biceps tissue between the two intensity groups in this study when the same fatigue criteria are used, which is an important consideration when using EIM to monitor changes as a result of fatigue and exercise related injury.